Clinical Spectrum and Severity of Poisoning in the Paediatric Intensive Care Unit of a Tertiary Care Centre in Uttarakhand: A Retrospective Cohort Study - Sanober Wasim (JCDR Research and Publications Private Limited, 2021)
Introduction: Acute poisoning causes significant mortality and morbidity among children worldwide. However, the pattern of poisoning and causative substances varies significantly in geodemographic areas. Aim: To describe admissions due to acute poisoning in the Paediatric Intensive Care Unit (PICU) of a tertiary care centre in terms of demographics, clinical profile, specific agents involved and severity of poisoning. Materials and Methods: This was a retrospective cohort study conducted in PICU of a tertiary care level teaching institute of Uttarakhand, India, over a period of three years on subjects of age group from one month to 18 years. Data was collected and analysed for demography, clinical presentation, substance, management, complications, and outcome. Poison Severity Score (PSS) was used to assess the severity of poisoning. Data was analysed using Statistical Package for the Social sciences (SPSS) software version 21.0. Results: During the study period, out of total 751 PICU admissions, 45 were due to poisoning. Organophosphates 20 (44%) and aluminium phosphide 12 (26%) were the most common substances used. Accidental poisoning was common 6 (46%) among less than five years of age. However, suicidal attempts were noted more frequently 20 (64%) among >15 years of age group. Vomiting 31 (69%), altered sensorium 23 (51%), and pain abdomen 16 (35%) were the most common presentations. Nine (20%) patients required ventilatory support as well. Three (6.6%) patients died; all associated with aluminium phosphide poisoning. Conclusion: The most common poison consumed is organophosphate. Aluminium phosphide is the most lethal poison, accounting for all the deaths in the study. Accidental poisoning is common in children less than five years of age. Suicidal poisoning is common among adolescents which must be prevented by early detection of stress. Primary health care facility hesitates to intervene even for basic poisoning care before referring.